Blinding Polyphemus: Geography and the Models of the World - Franco Farinelli (Seagull Books, 2018)
Today, we believe that the map is a copy of the Earth, without realizing that the opposite is true: in our culture the Earth has assumed the form of a map. In Blinding Polyphemus, Franco Farinelli elucidates the philosophical correlation between cultural evolution and shifting cartographies of modern society, giving readers an interdisciplinary study that attempts to understand and redefine the fundamental structures of cartography, architecture, and the notion of "space." Following the lessons of nineteenth-century critical German geography, this is a manual of geography without any map. To indicate where things are means already responding, in implicit and unreflective ways, to prior questions about their nature. Blinding Polyphemus not only takes account of the present state of the Earth and of human geography, it redefines the principal models we possess for the description of the world: the map, above all, as well as the landscape, subject, place, city, and space.